Contextualizing Abdurrahman Wahid's Liberation Theology Against National Resilience - Khafifatul Fian; Farichatul Maftuchah (Jurnal Ushuluddin, 2023)
The purpose of this study is to analyze theological thinking according to Abdurrahman Wahid. The type of research used is library research through data collection techniques by searching for sources either from articles, books, or other sources relevant to the topic of discussion. After the data is collected, then the selection researcher and then the analysis researcher. After analysis, the next stage is the last stage, namely drawing conclusions. The results showed that the theological thinking of Abdurrahman Wahid's perspective was divided into three discussions: pluralism, the pribumization of Islam, and neo-modernism. These three ideas have implications for national resilience such as pluralism which can create national strength because of the formation of an attitude of tolerance, mutual respect, respect, and a consistent philosophy in achieving goals. Islamic indigenization can develop national resilience through the formation of a dynamic, adaptive, and universal Islamic society or openness. Neo-modernism through an attitude of solidarity based on aspects of equality can create national resilience